Review of videolaryngoscopy pharyngeal wall injuries. (27th June 2016) - Greer, Devon; Marshall, Kathryn E.; Bevans, Scott; Standlee, Aurora; McAdams, Patricia; Harsha, Wayne
Abstract : Objectives: Reports of patient injuries associated with videolaryngoscopy are increasing in the literature. There are a wide variety of opinions regarding both safe use of the device and patient care following aerodigestive tract injury. We have seen an increase in videolaryngoscopy‐associated injuries in recent years at our institution. Because of this, we wanted to determine if video‐assisted laryngoscopy presents a greater risk of injury compared with direct laryngoscopy. Furthermore, we wanted to determine if there were patient and/or surgical factors that could contribute to patient injuries following videolaryngoscopy. Data Sources: MAMC anesthesia records, PubMed, Ovid. Review Methods: We compared rates of injury between videolaryngoscopy to direct laryngoscopy at our institution by searching anesthesia records to identify laryngoscopy procedures that resulted in injury to the soft palate or oropharynx. We also identified 19 published cases in the literature, in addition to our cases, that we reviewed for patient characteristics (e.g., body mass index, age and sex, Mallampati grade), type of videolaryngoscope, location of injury, and type of repair (if any) required. Results: At our institution, we have a statistically higher rate of injury using videolaryngoscopy compared to direct laryngoscopy. Our data also indicate that women are more commonly injured during videolaryngoscope intubation than men. The right tonsillar pillars and soft palate are the most frequently injured, with through‐and‐through perforation of the soft tissues being the most common type of injury. The most common repair of injuries required simple closures, and long‐term harm was very rare. Conclusion: Our data suggests that using video‐assisted laryngoscopy for intubation puts a patient at significantly greater risk for injury compared to direct laryngoscopy. Laryngoscope, 2016 127:349–353, 2017